1992
DOI: 10.1002/aja.1001940303
|View full text |Cite
|
Sign up to set email alerts
|

The changing architecture of the neonatal rat ovary during histogenesis

Abstract: The purpose of this study was to describe the changing histological organization of the rat ovary during postpartum days one through three (pl-p3). A PC-based image-combining microscope system was used to reconstruct the ovary in three dimensions. On pl, cylindrical pocket-like structures radiated from the core of the ovary that were open toward the surface epithelium. The walls of the pockets contained connective tissue cells and capillaries (stroma). By p2, these pockets had completely closed; each pocket en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
123
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(134 citation statements)
references
References 30 publications
8
123
1
Order By: Relevance
“…We noted that the superficial cortex particularly in day 1 ovaries shows smaller oocytes, many still in cell nests, together with primordial follicles. A similar sequence of primordial follicle formation suggesting a medullary-cortical gradient of maturation has been reported in the mouse ovary by Peters (1969) and McClellan et al (2003), the rat-(Hirshfield 1992, Rajah et al 1992, Hirshfield & DeSanti 1995 and the sheep ovary (Sawyer et al 2002) and appears to be a developmental pattern intrinsic to the neonatal mammalian ovary . As oocytes in the ovarian medulla mature earlier than those in the superficial cortex, i.e.…”
Section: Discussionmentioning
confidence: 77%
“…We noted that the superficial cortex particularly in day 1 ovaries shows smaller oocytes, many still in cell nests, together with primordial follicles. A similar sequence of primordial follicle formation suggesting a medullary-cortical gradient of maturation has been reported in the mouse ovary by Peters (1969) and McClellan et al (2003), the rat-(Hirshfield 1992, Rajah et al 1992, Hirshfield & DeSanti 1995 and the sheep ovary (Sawyer et al 2002) and appears to be a developmental pattern intrinsic to the neonatal mammalian ovary . As oocytes in the ovarian medulla mature earlier than those in the superficial cortex, i.e.…”
Section: Discussionmentioning
confidence: 77%
“…This is similar to other studies on the mouse and also on humans where oocyte loss has been observed during fetal development (De Pol et al 1997, De Felici et al 1999, McClellan et al 2003, Ghafari et al 2007). In the rat, follicles are first observed in the core of the ovary and formation gradually shifts toward the surface (Rajah et al 1992). The follicles closer to the medullary region are also the follicles that begin to develop first (Hirshfield & DeSanti 1995).…”
Section: The Process Of Follicular Assemblymentioning
confidence: 99%
“…Each primordial follicle is composed of a single oocyte arrested in the diplotene stage of the first meiotic division and surrounded by a single layer of squamous pre-granulosa cells. In rodents follicle assembly occurs in the first few days after birth (Peters & Byskov 1975, Cran & Moor 1980, Hirshfield 1991, Rajah & Glaser 1992. In humans, follicle assembly begins during midgestation near week 18 and continues into the third trimester (Baker 1963, Fulton & Martins da Silva 2005.…”
Section: Introductionmentioning
confidence: 99%